Aksentuasi Reinforcement Bagi Siswa Sekolah Dasar - Nuruddin Nuruddin (JUPE : Jurnal Pendidikan Mandala, 2022)
Accentuation of reinforcement, namely giving emphasis to students to always give a positive response, be it verbal or non-verbal so that it has feedback for students to always excel or always do good deeds. Accentuation of reinforcement in elementary school children is important, because children are still overshadowed by the world of games, so at their age they still need a lot of playing. On the other hand, they are faced with various disciplines, such as Mathematics, Indonesian, and other subjects. The purpose of accentuation reinforcement is to motivate and make children happy and happy when they are in a new educational world. Therefore, teachers are required to have the ability to accentuate reinforcement because every child has the instinct to get rewarded, so that their enthusiasm for school does not subside and can even become a joyful world.